Karakteristik Indeks Massa Tubuh Berdasarkan Jenis Kelamin dan Umur Pada Mahasiswa Program Profesi Dokter Fakultas Kedokteran Universitas Muslim Indonesia - Budiman, Budiman; Hamzah, Pratiwi Nasir; Musa, Inna Mutmainnah (Yayasan Citra Cendekia Celebes, 2022)
Background: Body Mass Index (BMI)isasimple tool orwaytomonitor the nutritional status ofadults, especially those related to underweight and overweight. BMI is defined as a person's bodyweightinkilogramsdividedbyhisheightinmeters(kg/m2). Objective: To determine the characteristics of BMI based on age and sex in the Medical ProfessionalProgram Students, FacultyofMedicine, MuslimUniversityofIndonesia. Methods: This research is a quantitative study with a cross sectional approach. Data collection wascarried out through questionnaires. The research sample was a sample with the overall BMI andcontrol was the ideal BMI sample. The sample obtained was 100 students of the Professional DoctorProgram, FacultyofMedicine, MuslimUniversityofIndonesia. Results:Theresultsshowedthattherewere10respondentswithunderweightBMIofwomen(10%),all of whomwere> 20 years oldwhile there were no men. Respondents with normal BMI are 49people(49%)aged≤20years,4people,>20yearsoldasmanyas45people,with14menand35women.RespondentswithBMIOverweight25people(25%)aged≤20years1person,aged>20years24peoplewith12men and13women.There were11 respondentswith BMIobese1(11%) aged≤20years1person,aged>20years10people,with9menand2womenand5respondentswithobese BMI 2 (11% ) aged ≤ 20 years 1 person, aged> 20 years 4 people with 3 men and 2 women.Conclusion:ThereisasignificantrelationshipbetweenBMIcharacteristicsbasedonsex,whileBMIcharacteristicsbasedonagehavenosignificantrelationship.